Remarks by World Bank Group President David Malpass to the U.S. Treasury’s Event on Tackling Food Insecurity : The Challenge and Call to Action - Malpass, David (World Bank, Washington, DC, 2022)
These remarks were delivered by the World Bank Group President David Malpass to the U.S. Treasury’s Event on Tackling Food Insecurity : The Challenge and Call to Action, on April 19, 2022. He spoke about Russia’s invasion of Ukraine has triggered major threats to global food and nutrition security. He mentioned that the global food and fertilizer prices were already on the rise prior to the war. He added that food and nutrition insecurity were also rising. He described that the deepening of the crisis in the last two months is directly linked to the terrible war being waged by Russia on Ukraine, and the costly financial, shipping, and logistical hurdles now faced by agribusinesses and importers. He also said that food crises are particularly devastating for the poorest and most vulnerable people. He expects to launch an overall surge in their financial support in coming weeks. He told them that funding for food security will be an important component. He also mentioned two mechanisms that can be mobilized alongside IDA and IBRD, to boost food security and resilience, in a well-coordinated manner as follows: (i) the Global Agriculture and Food Security Program (GAFSP), which was set up by the G20 in response to the 2007-2008 food crisis; and (ii) the World Bank also hosts a multi-donor Trust Fund, Food Systems 2030, that can help countries strengthen their food systems to meet short and long-term goals. He spoke about the tragedy unfolding in Ukraine must not be compounded with another tragedy – a global food crisis. He concluded by saying that they can count on the World Bank Group to work with all partners to help the people of developing economies to confront these challenges.